De novo design of therapeutic peptides and their characterization - Thakkar, Ravindra (Kansas State University, 2022)
Peptides are low-cost, flexible, and biocompatible and can be designed to serve various functions in biotechnology and medicine. Peptides can be designed such that they fold spontaneously and adopt a specific conformation under specific conditions, including when in contact with the three-dimensional structure of a protein or the two-dimensional structure of graphene. They are promising for design of functional materials for biotechnology and medical applications. I have studied peptide design for biotechnology, including peptide self-assembly on a graphene surface, and for medical applications such as cancer immunotherapy and treatment of coronavirus disease 2019 caused by SARS-CoV-2. In chapter 1, I describe my study of the self-assembly of a designed cyclic peptide on graphitic surfaces by molecular dynamics simulations. In experiments, it was found that hydrocarbon contaminants may interfere with this self-assembly, so we undertook a computational study of the behavior of these contaminants at the graphene–water interface and compared it to experimental data, as detailed in chapter 2. Peptides are also promising in medicine, particularly for inhibiting protein-protein interactions in situations where conventional small-molecule drugs can be unsuitable. Many viruses important for public health including SARS-CoV-2 and influenza enter cells by means of binding between viral proteins and cell surface proteins. The blockade of these undesirable protein-protein interactions has definite clinical significance. Another medical application where blocking protein-protein interactions is essential is the immune checkpoint blockade used in cancer immunotherapy. Immune checkpoint proteins most studied for cancer immunotherapy have flat and relatively hydrophobic interfaces that have impeded small-molecule drug development. Therefore, the application of peptide molecules that mimic the interacting surface of a natural binding protein is a promising alternative to small- molecule drugs. Immunotherapy activates the patient’s own immune system to treat cancer. When any foreign substance enters in the body, immune cells recognize it as a threat and neutralize it. But unfortunately, cancer cells often evolve to evade the immune system. Cytotoxic T-Lymphocyte Associated protein 4 (CTLA4) plays a crucial role in self-recognition and is an immune checkpoint protein that cancer cells may express to prevent attack from the immune system. Cancer cells frequently overexpress proteins of the B7 family, which allows them to evade the immune response by binding between these B7 proteins and CTLA4 on the surface of T cells. As presented in chapter 3, I have designed a 17-residue cyclic peptide targeting the CTLA4 protein that binds to it with a significant affinity. The binding activity was experimentally confirmed by the bio-layer interferometry (BLI) method. Studies performed by our collaborators showed an increase in CD8+ T cell-induced death of Lewis Lung Carcinoma (LLC) cells due to treatment with this peptide in vitro. In vivo, the designed peptide attenuated tumor growth in mouse models using orthotopic LLC cell allografts. A disease caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), called as COVID-19, has threatened global public health and the global economy. The WHO has reported 434 confirmed million cases and 6 million deaths. Although effective vaccines have been developed against SARS-CoV-2, many regions in the world still have a low rate of vaccination and even vaccinated individuals may experience reinfection. Deaths continue to be reported worldwide, exacerbated by continued mutation of the viral spike protein. SARS-CoV-2 enters the host cell through association of this spike protein, present on the envelope of the virus, and Angiotensin Converting Enzyme (ACE2), a protein expressed on the surface of host cells. As detailed in chapter 4, I have designed a 17-residue long peptide targeting the receptor-binding domain (RBD) of the spike protein to prevent COVID-19 infection. My designed peptide binds to the spike protein RBD with nanomolar affinity and blocks the binding site of ACE2. I have confirmed the binding activity using a microcantilever-based method and determined the dissociation constant using a BLI system. SARS-CoV-2 continues to mutate and produce variants. I have tested the binding activity of the designed peptide for the Delta variant, considered highly transmissible and declared as a variant of the concern (VOC) by the WHO. The BLI experiment revealed weaker binding of the designed peptide for the Delta variant spike protein compared to that for the original wild-type due to the mutations present in the receptor-binding domain of the spike protein.
Keywords: Computation peptide design; Protein modelling; Molecular dynamics simulations and free energy calculations; Cancer immunotherapy; Peptide drug development for COVID-19; Contaminants at graphene-water interface; Peptide self-assembly